Fuzzy Technique for Order Preference by Similarity to Ideal Solution Approach for Financial Efficiency Measurement of the Private Banks - Jana, Subrata; Giri, Bibhas Chandra; Sarkar, Anirban; Jana, Chiranjibe; Zavadskas, Edmundas Kazimieras (Transformations In Business & Economics, 2025)
In India, the banking industry has been one of the most rapid growing industries after the government’s demonetisation move in 2016. Private banks are doing exceptionally well in terms of their customer relations and financial services compared to the public banks. The main component of a bank is undoubtedly its financial performance. In today’s increasingly more competitive market, an appropriate and accurate measurement of financial performance is of great importance for a bank that aims to successfully maintain its market position. The main objectives of this study are to identify the best private bank and to rank the private banks in India. This research paper attempts to propose a Multi-Criteria Decision-Making (MCDM) model to evaluate and compare the financial performance of ten private banks enlisted on the National Stock Exchange (NSE) NIFTY as of 2 September 2023. These ten private banks are evaluated to gain a financial performance score and a ranking by applying a Fuzzy Technique for Order Preference by Similarity to Ideal Solution (F-TOPSIS) methodology, which is based on Euclidean Distance. The results show that the HDFC Bank is the most financially efficient one followed by ICICI Bank and Axis bank.